Meconium‐stained amniotic fluid and the need for paediatrician attendance. (5th November 2012) - Maayan‐Metzger, Ayala; Leibovitch, Leah; Schushan‐Eisen, Irit; Strauss, Tzipora; Kuint, Jacob
Abstract Aim To determine perinatal parameters among term newborn infants born by vaginal delivery with meconium‐stained amniotic fluid (MSAF) that needed paediatrician assistance. Methods Paediatricians who were in attendance in the delivery room due to MSAF among term infants completed 775 reports regarding the infants' delivery conditions, and the assistance provided. We defined 'paediatrician attendance needed' for a subgroup of infants for whom we retrospectively determined that paediatrician attendance in the delivery room was required. Results 'Paediatrician attendance needed' was determined in 31 (4%) cases. Among cases with documented normal foetal monitor, only 10 (1.8%) were defined as 'paediatrician attendance needed', a percentage significantly lower than among infants born following non‐reassuring foetal monitor: 21 (9.7%) (p < 0.001). 'Paediatrician attendance needed' was predicted by non‐reassuring foetal monitor [OR 6.02 (CI 2.72–13.31), p < 0.001], maternal fever [OR 6.34 (1.92–20.92), p = 0.002] and younger maternal age (for every year) [OR 0.889 (CI 0.82–0.96), p = 0.003]. Conclusions Term newborn infants born by vaginal delivery with MSAF with documented normal tracing foetal monitor are at low risk of the need for paediatrician assistance. Paediatrician attendance in the delivery room in labour involving MSAF should be recommended when non‐reassuring foetal monitor tracing is observed and should also be considered when maternal fever is recorded, and/or thick meconium is observed.